Colección helmintológica del Museo de La Plata: I. catálogo de preparaciones microscópicas, material tipo y no tipo - Sutton de Licitra, Carola Ana (2000)
Slides refered to 106 helminth species, 11 Temnocephala, 1 Aspidogastrea, 11 Monogenes, 77 Digenea, 5 Cestoda and 1 Acanthocephala, held in the La Plata Museum helminthological collection are ctalogued. Species are organized according to their main taxonomic group and listed alphabetically according to the their original name. The registration number, indication of type rank, host, localization, locality is included. The original biliographic references where the specimens have been described are given, and when necesary supplementary references added. last, the cataloque is complemented with alphabetical list of 70 genera, of 100 helminth species and the 104 hosts included. In complience with Reccomentation 72D od the International Code of Zoological Nomeclature this catalogue includes type specimens in this collection aa no previous one has ever been published.